Improved pasireotide response in USP8 mutant corticotroph tumours in vitro. Issue 8 (29th June 2022) - Albani, Adriana; Perez-Rivas, Luis Gustavo; Tang, Sicheng; Simon, Julia; Lucia, Kristin Elisabeth; Colón-Bolea, Paula; Schopohl, Jochen; Roeber, Sigrun; Buchfelder, Michael; Rotermund, Roman; Flitsch, Jörg; Thorsteinsdottir, Jun; et al.
Abstract : Cushing's disease is a rare but devastating and difficult to manage condition. The somatostatin analogue pasireotide is the only pituitary-targeting pharmaceutical approved for the treatment of Cushing's disease but is accompanied by varying efficacy and potentially severe side effects. Finding means to predict which patients are more likely to benefit from this treatment may improve their management. More than half of corticotroph tumours harbour mutations in the USP8 gene, and there is evidence of higher somatostatin receptor 5 (SSTR5) expression in the USP8-mutant tumours. Pasireotide has a high affinity for SSTR5, indicating that these tumours may be more sensitive to treatment. To test this hypothesis, we examined the inhibitory action of pasireotide on adrenocorticotrophic hormone synthesis in primary cultures of human corticotroph tumour with assessed USP8 mutational status and in immortalized murine corticotroph tumour cells overexpressing human USP8 mutants frequent in Cushing's disease. Our in vitro results demonstrate that pasireotide exerts a higher antisecretory response in USP8-mutant corticotroph tumours. Overexpressing USP8 mutants in a murine corticotroph tumour cell model increased endogenous somatostatin receptor 5 ( Sstr5 ) transcription. The murine Sstr5 promoter has two binding sites for the activating protein 1 (AP-1) and USP8 mutants possibly to mediate their action by stimulating AP-1 transcriptional activity. Our data corroborate the USP8 mutational status as a potential marker of pasireotide response and describe a potential mechanism through which USP8 mutants may regulate SSTR5 gene expression.